Analisis Sentimen Mengenai Keberhasilan Indonesia di Ajang Thomas Cup 2020 (Studi Kasus Media Sosial Twitter) Menggunakan Metode Naïve Bayes dan Decision Tree - Muhammad Andi Ramadhan; Muhammad Iwan Wahyudin (KITA Institute, 2022)
The Indonesian men's badminton team won the 2020 Thomas Cup after defeating China in the final. The final match of the Thomas Cup 2020 between Indonesia and China took place at Ceres Arena, Aarhus, Denmark. As a result, Indonesia won 3-0 over China. On social media twitter, Indonesia's success in the Thomas Cup 2020 event has become one of the most discussed topics due to the large number of supports and opinions from various circles of society. Some opinions from the public on Twitter will be used as sentiment analysis public opinion to reSearch data regarding Indonesia's success in the 2020 Thomas Cup. This reSearch uses the Naïve Bayes and K-NN methods which are expected to have a good level of accuracy. According to several studies, the Naïve Bayes method has an accuracy rate of 95.161%, while the Decision Tree method has an accuracy rate of 84.677%.